Analysis of Schottky emission electric charge transport mechanism in Cu-Lu2O3-Cu MIM structure by temperature dependent current-voltage characteristics. (November 2019) - Akbar, Shahnaz; Jacob, Jolly; Mahmood, Khalid; Wasiq, M.F.; Jaffari, Ghulam Hassnain; Khan, Muhammad Azhar
Abstract: In this study, the Cu-Lu2 O3 -Cu metal-insulator-metal (MIM) structure was fabricated by electron beam evaporation method on the glass substrate with symmetric electrode configuration. The dominant conduction mechanism in fabricated MIM diode was analyzed using temperature dependent current-voltage (I-V) characteristics in temperature range 323–403 K. Schottky emission, Fowler-Nordheim (F-N) and Poole-Frankel (P-F) conduction mechanisms were tested by analyzing the I-V data according to these theories. P-F emission and Schottky emission conduction mechanisms were found to be dominant conduction mechanisms in low and high applied electric field range respectively. The Schottky emission mechanism was further studied in detail by plotting the Ln(I/T 2 ) Vs V 1/2 and Ln(I/T 2 ) Vs 1000/T plots at different applied fields and temperatures respectively. The dielectric constants were extracted from the conduction plots at various temperatures and were found to be close agreement with experimental dielectric constant of Lu2 O3 (11). The metal-insulator barrier height and trap energy were also calculated at various measurement temperatures and discussed according to Schottky emission theory. Highlights: Growth of Cu-Lu2 O3 -Cu MIM structures on glass substrate by electron beam evaporation. Investigation of charge transport mechanism in Cu-Lu2 O3 -Cu MIM structure using temperature dependent I-V characteristics. Various conduction mechanisms models have been tested to probe the real charge transport mechanism. Data confirmed that Schottky emission is the dominant transport mechanism in Al-Gd2 O3 -Al structure. The field dependent Ln(I/T2 ) vs 1000/T plots were obeyed a linear relationship according Schottky emission theory.